EFISIENSI RANTAI PASOK DALAM INDUSTRI ROSTER BETON: PERBANDINGAN METODE ECONOMIC ORDER QUALITY DAN JUST-IN-TIME - Safitri, Khoerun Nisa; Fole, Asrul; Aini, Nurul (LPPM Universitas Ibnu Sina, 2025)
This study aims to analyze supply chain efficiency in the concrete roster industry in Batam by comparing the Economic Order Quantity (EOQ) and Just-In-Time (JIT) methods with the conventional inventory approach. The main issue faced by the industry is the high total inventory cost due to suboptimal ordering frequency and significant storage expenses. The data used are actual production figures and raw material requirements throughout 2024. A quantitative approach was applied using EOQ and JIT calculations. The results show that the EOQ method generates an annual inventory cost of Rp7,595,000, which is significantly lower than that of the JIT method at Rp10,400,000 and the conventional method at Rp145,650,000. EOQ proves to be more efficient by optimizing order quantities and minimizing storage costs. In contrast, the JIT method effectively eliminates storage costs but increases ordering costs due to more frequent orders. This study recommends adopting the EOQ model as an efficient inventory management solution for medium-scale manufacturing industries. The findings are expected to serve as a reference for strategic decision-making in logistics and supply chain management.